Pemikiran KH. M. Sholeh Bahruddin dan Praktiknya dalam Toleransi Beragama di Pondok Pesantren Ngalah Pasuruan (The Thought of KH. M. Sholeh Bahruddin and His Practices in the Religious Tolerance in Pondok Pesantren Ngalah Pasuruan) - Ahmad Wasil; Muhammad Tajuddin (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACT Understanding religious tolerance from the perspective of kiai Sholeh is that basically religion presents on earth as a guide and conveyer of peace for people. The purpose of this research is to determine the religious tolerance from the perspective of KH. M. Sholeh Bahruddin and to explore the practice. This research is a type of qualitative research with a phenomenological approach and the theory of structural functionalism by Talcott Parsons where data sources classified as primary and secondary data. The data collection techniques applied in this study are participant observation, in-depth interviews and documentation studies. In this study, the data analysis process includes data reduction, data presentation and conclusions. The results of the study discover that religious tolerance from the perspective of kiai Sholeh are derived from the commands of the Qur'an and hadith, orders from parents and teachers, the application of the ideology of Ahlus Sunnah wal Jamaah. Kyai Sholeh's practice of religious tolerance in Sufism includes the application of Galak Gampil's fiqh law, and peaceful behavior towards anyone. This reflected in his da'wah with the method of